Chemical interactions in composites of gellan gum and bioactive glass: self-crosslinking and in vitro dissolution - Astanina, A.; Koivisto, J. T.; Hannula, M.; Salminen, T.; Kellomäki, M.; Massera, J. (Frontiers in Chemistry, 2023)
We investigated the interactions between the organic-inorganic phases in composites and the impact on in vitro dissolution. The composite consists of a hydrogel-forming polysaccharide gellan gum (GG, organic phase) and a borosilicate bioactive glass (BAG, inorganic phase). The BAG loading in the gellan gum matrix was varied from 10 to 50 wt%. While mixing GG and BAG, the ions released from BAG microparticles crosslinked carboxylate anions of GG. The nature of the crosslinking was assessed and its impact on mechanical properties, swelling ratio, and enzymatic degradation profile, upon immersion for up to two weeks was studied. Up to 30 wt% of BAG in GG caused an increase in mechanical properties, associated with increasing crosslinking density. At higher BAG loading, excess divalent ions and percolation of particles led to a decrease in the fracture strength and compressive modulus. Upon immersion, a decrease in the composite mechanical properties was attributed to the dissolution of the BAG and the loosening of the glass/matrix interface. The enzymatic degradation of the composites was inhibited at higher BAG loadings (40 and 50 wt%) even when specimen was immersed for 48 hours in PBS buffer with lysozyme. During the in vitro dissolution in both SBF and PBS, the ions released from the glass led to the precipitation of hydroxyapatite already at day 7. In conclusion, we thoroughly discuss the in vitro stability of GG/BAG composite and established the maximum BAG loading, to maximize the GG crosslinking and mechanical properties. Based on this study, 30,40, and 50 wt% of BAG in GG will be further investigated in an in vitro cell culture study.